The effect of private consumption, capital inflows and trade balance towards inflation in Malaysia (1976-2006) / Siti Norain Abdullah - Abdullah, Siti Norain (2007)
The aim of this study is to identify the relationship between dependent variable which is inflation with independent variables which are private consumption, trade balance and capital inflows. Besides that, this study also to identify the causality effect between dependent and independent variables. The scope of this study is within Malaysia. This study uses annually data for 30 years which are from the year 1976 to the year 2006. The collected will be analyzed using computer software which is known as SPSS. The analysis is carried out based on the multiple regression and Granger causality. There are some previous researchers have concluded that there are positive relationship between inflation with private consumption, trade balance and capital inflows There are also some of the researchers says inflation give causality effect between inflation and other variables.